Usability Testing dalam Pengujian Antarmuka Website Payment - Trise Putra, Dede Wira; Syafutra, Willdo (Jurnal Teknik Informatika dan Elektro, 2023)
E-counters provide online features using a laptop or smartphone device connected to the internet for payment transactions. Users of this application are quite high with the number of samples to be taken 100 respondents. The tests carried out refer to the analysis of the influence of user friendly indicators, namely usefullness, ease of use, ease of learning and satisfaction survey. Based on the results of the study it was found that the indicator of ease of learning on memorability has a negative value because there is no impact on other indicators. From the research that has been done, it is found that efficiency indicators can be seen which have high results.